The Analysis Of English Teachers’ Strategies On Online Classes During Covid-19 Pandemic : English Teaching Strategy, Online Learning - Rustam, Singka; Nurlaela (RITMA: Journal of Islamic Integrated Research, Science, and Community, 2024)
The pandemic of COVID-19 siuation causes the Indonesian government announce the learning activities into online learning. This policy and its relation to teachers’ strategies in teaching are interesting to be analyzed. The aims of this research is to find out kind of English teaching strategies and the advantages of these strategies on online classes at Mts. Nurul Aeyn Asadiyah Kampung Baru in academic year 2020/2021. This research used descriptive qualitative approach and involved two English teachers as the participant, while the instrument used to collect data were interview, observation and documentation. The result of this research shows that there are several kind of English teachers’ strategies used on online classes at Mts. Nurul Aeyn Asadiyah Kampung Baru, were as follows: 1). Direct strategy (lecture and didactic question); 2). Indirect strategy (Inquiry learning); 3). Interactive strategy (group assignment); 4). Experiential strategy (playing games); and 5). Independent strategy (Homework). Futhermore, these strategies used by the teachers is beneficial for both teacher and students, were as follows: 1). Teaching strategy is effective and flexible way in conveying the material and able to improve students’ knowledge; 2). To determine students’ knowledge in order that they actively participate in learning activity; 3). Increasing cooperation between students; 4). Students more active not getting bored and interested in learning activity; and 5). Increasing students’ knowledge and students’ independency.